أثر الإيقاع في تشكيل النّص الشّعري عند سعيد قندقجي (Journal of Hama University, 2025)
of loss, prepare the way for joy,    Qandekji, relying on the buoys: "The journey do not break the dilemmas,cushions and blooms, in your name, Love, holy stone, hanging on the wall of Arab time, trying to disperse its. importance and effect in the form of ignor.                                                                       The serch revealed the role of rhythm in clarifying the meaning and attracting the recipient to follow up on reading and its interaction with the poetry text, He also reached the point of my hotel to recruit most of the considered rhythms.Key words: Formation,Poetry text, Rhythm